Te Pītau o te Tuakiri: Affirming Māori Identities and Promoting Wellbeing in State Secondary Schools - Rata, Arama (2012)
Numerous researchers have posited links between ethnic identity and psychological wellbeing (Phinney, 1992; Martinez & Dukes, 1997; Roberts, Phinney, Masse, Chen, Robers, & Romero, 1999; Houkamau & Sibley, 2011), and Māori cultural interventions have been suggested as a means of promoting a range of positive outcomes (e.g. M. Durie, 1998; Durie, 2003b; Lawson-Te Aho, 1998). However, longitudinal evidence of causal pathways between Māori ethnic identity and psychological wellbeing remains scarce, and evidence of the positive impacts of cultural interventions is not well documented. The present thesis investigates Māori identity development in the context of State secondary schools, and explores the relationships between Māori cultural engagement, Māori identity, and psychological wellbeing. A methodology that incorporates both mātauranga Māori (Māori knowledge) and Western scientific knowledge bases and research methods was applied. Interviews were held with Māori students and their whānau (families) at a State secondary school where a community-driven initiative to improve Māori student outcomes took place. Thematic analysis was used to generate Te Korowai Aroha Framework, outlining how Māori cultural initiatives can enable schools to fulfil their duty of care and meet Māori community needs by affirming individuals‟ cultural identity and agency, by building relationships based on mutual respect, and by working collaboratively within the school and with external services providers. Thematic analysis of these interviews was also conducted to generate The Pōwhiri Identity Negotiation Framework. The pōwhiri (formal welcome), in which Māori creation narratives are ritually re-enacted, is used as a metaphor for Māori identity negotiation. The stages of creation Te Kore, Te Pō, Te Whaiao, and Te Ao Marama are used to describe, respectively: those who were yet to display interest in Māori cultural identities; those who were interested in developing their Māori identities; those who were actively exploring their Māori identities; and those who felt secure in their Māori identities. Quantitative longitudinal survey data from over 300 Māori adolescents in the Youth Connectedness Project was then analysed. Structural Equation Modelling revealed that Māori cultural engagement positively predicted Māori ethnic identity, and that Māori ethnic identity positively predicted psychological wellbeing, in support of hypotheses. In addition, Hierarchical Linear Modelling revealed that the higher a school‟s level of Māori cultural promotion, the higher the ethnic identity of its students was likely to be. The results of this thesis demonstrate the impact of school cultural environments on individual identity development, and provide evidence that cultural engagement initiatives can enhance Māori identities, which in turn can increase psychological wellbeing. The results from the studies presented in this thesis are incorporated into Te Pītau o te Tuakiri framework, outlining how Māori identities can be nurtured, and the results are also used to offer guidelines for individuals wishing to become more engaged in Māori culture, and institutions wishing to become more responsive to Māori communities. These findings are used to challenge educators and policy makers to ensure schools and other State institutions support Māori cultural expression and affirm Māori identities.
Keywords: colonisation; education; identity; policy; wellbeing

Voting in Māori Governance Entities - Bargh, Maria; Rata, Arama (The International Indigenous Policy Journal, 2020)
Internationally, declining voter turnout is a topic of considerable concern in many liberal democracies. In this article, we investigate whether these similar trends can be discerned in the voter turnout for Māori governance entities. We first explore some of the demographic contexts within which Māori governance entities operate with a specific focus on population, residence, and age. We then provide a detailed descriptive analysis of voting data from one particular entity: Te Rūnanga o Ngāti Awa, with whom we worked to understand how their elections inform their aspirations for continuing connectedness with tribal members. In the final section of the article, we present findings from an analysis of publicly available tribal voting data to see whether the trend of declining voter turnout is observable and whether online voting is shown to impact turnout.
Keywords: iwi elections; kaupapa māori research; māori voting; online voting; post-settlement (waitangi tribunal); self-determination

Whakawhanaungatanga as a Māori Approach to Indigenous–Settler of Colour Relationship Building - Rata, Arama; Al-Asaad, Faisal (New Zealand Population Review, 2019)
Communities of colour are racialised and oppressed differentially by settler colonial states (Saranillio, 2013), yet the discourse of diversity and inclusion that dominates state interactions with communities of colour tends to conflate marginalised groups as equivalent and interchangeable to the detriment of intergroup relations. An approach to community building that recognises racial difference in general and the irreducibility of indigeneity in particular is needed if racialised communities are to create solidarities for transformative change. We engage Indigenous and settler colonial theories to address these imperatives, while noting the distinct character of these frameworks. In particular, we seek to highlight the specificity of indigeneity in settler colonial contexts, such as Aotearoa New Zealand, and to generate a model for relationship building that is not founded on settler colonial ideologies, by drawing on Indigenous concepts. Through thematic analysis of interviews with Māori community leaders, we explore Māori-–tauiwi (settler) of colour (ToC) relations. The results of our qualitative analysis provide evidence for Māori–ToC relations that are consistent with whanaungatanga (good relationships characterised as family-like, based on similar experiences, and bound in conditional solidarity; see Benton, Frame, and Meredith, 2013). Furthermore, we identify the following four aspects of whakawhanaungatanga (relationship building): positioning, power sharing, dialogue and cultural practice. Thus, we suggest whakawhanaungatanga as a Māori approach to relationship building with the potential to generate Indigenous–settler of colour solidarities towards transformative change.
Keywords: colonisation; diversity; relationship building; whanaungatanga

Māori Sovereignty or Death - Rata, Arama; Brayne, Gabriella; Barber, Simon (Decolonization of Criminology and Justice, 2023)
In her 1984 book ‘Māori Sovereignty’, Donna Awatere sustains a blistering polemic on ‘white culture’ that still retains its rhetorical force 40 years later. Her construction of a sharply delineated binary between a monolithic notion of ‘white culture’ as against ‘taha Māori’ can come at the cost of simplification. But this is not at all to say that Awatere is wrong when she says it is ‘Māori Sovereignty or death’. In this paper, we extend Awatere’s work by analysing relationships between colonialism and capital. We begin by situating Awatere’s work in its historical context, outlining major shifts in the global political economy, and drawing on Awatere’s analysis of Fascism to account for contemporary Far Right movements. Building from the inextricability of Fascism from the settler colonial/imperialist economy, we explore Awatere’s framing of whiteness as a system of racial exploitation and violence that enforces the state’s genocidal claims to sovereignty, defined through necropower – capitalism’s consumption of racialised death. We then consider the contradictions between capitalism and constitutional transformation. By scanning revolutionary movements elsewhere (in particular the Chilean movement for plurinationalism), we identify the need for extra-parliamentary, broad-based, popular power and constituent authority from below, as well as Indigenous solidarities and international alliances to circumvent anti-Māori populism and confront capital. In reflecting on the power of death, and the need for counter-hegemonic culture capable of securing the transition out of capitalism, we are drawn to the revolutionary essence of whakapapa as an Indigenous ontology that eternally resists necropower.